Influence of the brand on price and design (Dimensión Empresarial, 2019)
The purpose of this investigation is to confirm that brands are more influential than the price and the design in the purchase decision making of fashion products. For this, two quasi-experiments were applied to Peruvian millennials. It is shown that this segment is loyal to brands, but not to all its product categories, because the price and the design may be more relevant in the purchase of some of these in specific. In this way, it is determined that brand equity or the value of a fashion brand may vary depending on clothing types.